Nurses’ Attitude on The Use Of Personal Protective Equipment (PPE) in Emergency Room of dr. Slamet Hospital Garut - Moch Panji Khoerudin; Kurniawan Yudianto; Iwan Shalahuddin (Journal of Nursing Care, 2020)
Nurses in the emergency room have direct contact with patients. This contact can potentially lead to the risk of nosocomial infections or Healthcare-acquired Infections (HAIs). One of the efforts to avoid this infection is through using personal protective equipment (PPE). The attitude of nurses can influence the use of PPE when giving nursing care to patients. This is in line with the theory of attitude which says that individual attitudes are the beginning of the realization of individual actions or behavior. This study was aimed at finding out emergency department nurses’ attitude in using personal protective equipment. The research design used was descriptive quantitative. 50 nurses were selected as samples using total sampling technique. In collecting the data, the instrument used was attitude questionnaire which had been modified into attitude component classifications such as cognitive, affective, and conative. The research instrument was tested for validity of 0.5431-0.6754 with r table 0.4438, and the results of the Cronbach reliability test were 0.805. Univariate data analysis is presented in the results of frequency distribution in the form of a percentage. This study showed 26 respondents (52%) had negative attitudes from the affective and conative components (responses from nurses who neglected the use of personal protective equipment (PPE) to prevent work accidents. While positive attitudes were in the cognitive component, 31 respondents (62% ). This study concludes that emergency department nurses’ attitude towards the use of PPE was negative based on affective and conative components but they responded positive attitude on cognitive component. The policy concerning on the use of PPE for the nurses need to be increasingly supervised as an effort to keep safety and health for both patients and nurses.